Proposta de uma ferramenta para análise da competitividade de destinos turísticos pela abordagem de redes de empresas - Barros, Rodrigo de (2013)
This research aimed to develop a Model for Measuring Competitiveness in Tourism Products by approach of business networks. For this purpose it was used a literature review about characteristics of the tourism sector, clusters, business networks, cooperation and competitiveness. Thereafter, it was developed the construction of a new framework which was built through bibliometric analysis with the use of keywords aligned and delimited to the topic of research, aiming a database that provides the necessary scientific equipment to the model development. This new database was generated from only articles published between the years 2002 and 2012 which appeared in “Periódicos Capes” with access at Federal Technological University of Paraná. These publications are based for building the model presented here, which consists of eleven dimensions, fifty-nine critical factors, one hundred fifty-five variables, sixty hundred and five assumptions and five hundred eighteen indicators. For each indicator is assigned a scale from zero to one, and the averaged across all performance indicators in the result of competition for each of the eleven dimensions. Thus, the averaged results in eleven dimensions called Tourism Macro Competitiveness Index. These structural features of the tool allowed the same be characterized as comprehensive and targeted specifically for tourism products originated regionalization and cooperation. That is, the tool has interdependent dimensions for analysis of competitive macro destination in question, while the dimensions are dependent for more specific analysis, for example. Finally, it is noteworthy that although the model is structured by calculating the average of the indicators and dimensions, it is understood that a new quantitative approach to the model is possible, seeking even more effective results on the measurement of competitiveness.